Juridical Overview of the Prohibition of Interfaith Marriage from the Perspective of Human Rights and Criminal Law in Indonesia - Mohd. Yusuf DM; Saragih, Geofani Milthree (Kirana Publisher (KNPub), 2022)
Indonesia is a country that is famous for its multiculturalism, one of which is religion. Consequently, in living their lives, Indonesian people are faced with differences in various things, ranging from culture, way of life and interactions between individuals. The concern of the government and other components of the nation is the issue of inter-religious relations. One of the problems in inter-religious relations is the issue of mixed marriages (inter-religious marriages), which in this article are referred to as “interfaith marriages”. The condition of the pluralistic Indonesian society makes the association in society wider and more diverse. This has resulted in a more dynamic shift in religious values ​​than what happened in the past. In fact, interfaith marriages in Indonesia are not justified based on positive national law that applies in the territory of Indonesia. It can be concluded that if the State legalizes interfaith marriages in Indonesia, the State is tantamount to violating the existing religious laws in Indonesia, and violating Article 29 of the 1945 Constitution which guarantees every citizen to embrace religion and worship according to their religion and belief, while Each religion has different procedures for marriage or worship. The view of human rights in Indonesia should refer more to the human rights arrangements contained in the 1945 Constitution, not to the UDHR which we ourselves do not know who made it and even what the agenda is for a country that is still very religious. Human rights in Indonesia, not secular human rights, which separate religion from the state, which legalize all means in the name of